A Novel Hybrid UE Selection Scheme for Efficient Data Offloading Using D2D Communication. (12th June 2020) - C G, Balaji; A, Anu Monisha; K, Murugan
Abstract: The exponential growth in mobile broadband data traffic with demand for faster data connectivity has become the most engaging challenges for mobile operators. They are facing an enormous data load in the core network and are finding new solutions to offload data to other complementary technologies. Mobile data offloading using device-to-device (D2D) communication stands out as the promising and the low-cost solution to reduce the burden on cellular network. Data offloading is the process of reducing the load in the cellular medium by using alternative wireless technologies for bearing data using opportunistic assignment of nodes. In this paper, iNHeRENT, a Novel HybRid user equipment (UE) selection scheme using D2D communication in next generation wireless networks that provides better offloading efficiency and throughput than the existing schemes, is proposed. Here, a small set of Wi-Fi-enabled hybrid user equipment (UE_H *) is chosen to offload cellular data in an efficient way. The objective of the work is to use minimum number of UE_H * to cover maximum number of UE in the serving area of an evolved Node B and to offload maximum amount of data. A UE_H * is a special UE with both cellular and Wi-Fi interfaces enabled to offload data. The coverage, throughput, packet delivery ratio and offloading efficiency metrics for the selected number of UE_H * are considered, and it is found that an offloading efficiency of 95.45% was achieved for a minimum number of 7% UE_H * using iNHeRENT.